Claiming Space Locations and Orientations in World Literatures - Ekelund, Bo G.; Mahmutović, Adnan; Wulff, Helena (Cosmopolitan-Vernacular Dynamics in World Literatures, 2021)
This open access book explores literary works and practices - always existing in the dynamic relation between locations and orientations - in a series of carefully designed case studies. Explicitly expressed or implied, manifesting itself sometimes as dislocation and disorientation, the claiming of space by any symbolic means necessary is revealed as a constant effect of literary endeavors. In dialogue with geopolitics of culture, sociology and anthropology, attention to literary locations and orientations brings spatial particularity into the study of world literatures. These case studies demonstrate that four key terms (cosmopolitan, vernacular, location, orientation) can frame analyses of very different types of literary acts and texts in the contemporary period, allowing for distinctions that are not captured within the grids of other conceptual pairs like centre-periphery, local-global, postcolonial-metropolitan, North-South. With this framing, expressive practices in a wide range of regions - including Europe, Africa, the Middle East and the Pacific - are analysed in ways that bring out how spatiality is at stake in the cosmopolitan-vernacular dynamic. The open access edition of this book is available under a CC BY-NC-ND 3.0 licence on www.bloomsburycollections.com. Open access was funded by Riksbankens Jubileumsfond.